Pengaruh Kualitas Layanan Terhadap Trust Melalui Kepuasan Nasabah Di PT Bank Pembangunan Daerah Jawa Barat dan Banten Tbk KCP Buah Batu Bandung - Setyawan, Putri Jasmine Aprilia; Rahmi, Palupi Permata (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to find out how much influence service quality to trust through customer satisfaction. The sample used was 100 respondents. This study uses validity test, reality test, classical assumption test, path analysis test, hypothesis test (t test) and F test (Multan test) which are prepared using SPSS. Based on the results of the descriptive analysis, it can be seen that the variables of service quality (x), customer satisfaction (Y) and Trust (Z) are included in the very good category. The results of the determination coefficient showed that the contribution of service quality to customer satisfaction was 64.7%, the remaining 35.5% was influenced by other factors that were not studied. In addition, from the results of the study, it can be seen that the service quality variables (X) and Trust (Z) have a partial effect on customer satisfaction (Y), the service quality variables (X), and Trust (Z) have an effect on customer satisfaction (Y).